Studying the Effect of Hybrid Reinforcement with Particles from Silicon Carbide and Alumina on some of Mechanical Properties of Aluminum Alloy 6063: دراسة تأثير التدعيم الهجين بدقائق من أوكسيد الألمنيوم وكربيد السيلكون على بعض الخواص الميكانيكية لسبيكة الألمنيوم 6063 - Mootaz EzAlddin Al husaria, Fouad Dahiye, Al Mohanad Makki (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2021)
Metal matrix composite (MMC) is new engineering materials that contain two or more materials with different properties one being metal and the other may be metal, ceramic, glass reinforced materials. Aluminum metal-matrix composites are being used as materials for automobile and aerospace applications. So in This present article, We try to prepare hybrid composite materials based on aluminum alloy (6063) (AL- Mg-Si) and reinforce it by shared particles having the size of micron of silicon carbide (7.5 wt%) and Alumina particles are added in specific countrified parentage (2.5, 5, 7.5, 10 wt%) by stir casting technique to obtain hybrid Aluminum Which having the improving mechanical properties. After that inspections and mechanical tests have been done on all reinforcement samples. The results of tests have shown the Hardness, Ultimate tensile strength, and Impact toughness were determined; with the addition of reinforcement the properties are improved compared to the parent metal Aluminum (6063) alone. Based on the evaluation (7.5 % SiC +7.5 AL2O3 %) gives a better result as compared to other composition and demonstrated superior hardness (87.74Hv), Impact toughness (18 Joul), and Ultimate tensile strength(218.9 Mpa).